1993
DOI: 10.1029/92tc02773
|View full text |Cite
|
Sign up to set email alerts
|

The Coast Belt Thrust System: Evidence of Late Cretaceous shortening in southwest British Columbia

Abstract: The Coast Belt Thrust System (CBTS) is the leading edge of a west vergent contractional belt that formed along the inboard margin of the Insular superterrane in late Cretaceous time. The foreland of this contractional belt comprises a system of east dipping frontal thrusts that imbricate Jurassic and Early Cretaceous supracrustal arc sequences and related plutonic suites of the Westem Coast Belt (WCB). These faults root eastward into an imbricate zone of folded thrusts and out-of-sequence reverse faults across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 40 publications
0
80
0
Order By: Relevance
“…Regional midCretaceous deformation is recognized in British Columbia (BC: Fig. 2), with, for example, ocean-vergent thrusting (Journeay & Friedman 1993) of upper Valanginian to middle Albian volcanic rocks. Thrusting was active from at least mid-Albian times to the emplacement of synkinematic plutons dated at ~97 Ma and ~96 Ma and deformed an accretionary complex that formed prior to 92 Ma (Chardon 2003).…”
Section: North Americamentioning
confidence: 99%
“…Regional midCretaceous deformation is recognized in British Columbia (BC: Fig. 2), with, for example, ocean-vergent thrusting (Journeay & Friedman 1993) of upper Valanginian to middle Albian volcanic rocks. Thrusting was active from at least mid-Albian times to the emplacement of synkinematic plutons dated at ~97 Ma and ~96 Ma and deformed an accretionary complex that formed prior to 92 Ma (Chardon 2003).…”
Section: North Americamentioning
confidence: 99%
“…The Methow terrane was imbricated structurally with the Bridge River and Cadwallader terranes along its western margin during Cenomanian time ( Figs. 1 and 4; Journeay and Friedman, 1993). Along the eastern margin of the Methow terrane, the Pasayten fault has a multistage deformational history that includes Late Cretaceous sinistral displacement, Late Cretaceous to Tertiary west-vergent contractional motion, and Tertiary extension (Hurlow, 1993).…”
Section: Structural Settingmentioning
confidence: 99%
“…A west-vergent fold-thrust belt, that developed around 100 Ma (Rubin et al 1990;Haeussler 1992), places highgrade rocks of the eastern belt over lower grade rocks of the Gravina-Dezadeash-Nutzotin belt to form a thrust stack that is of higher metamorphic grade upwards (Lynch 1992(Lynch , 1995Journeay and Friedman 1993;Crawford et al 2000;McClelland and Mattinson 2000). Although the deformation is about the same age, the polarity is the reverse of the more southerly batholiths.…”
Section: Comparison With Other Cordilleran Batholithsmentioning
confidence: 99%
“…Similarly, detailed field studies and geochronology within the Coast batholith of Canada and southeastern Alaska led to the realization that it too could be readily divided into two parts, there separated by the collapsed Nutzotin-Dezadeash-Gravina basin and related fold-thrust belt (Rubin et al 1990;Journeay and Friedman 1993;Gehrels et al 2009). And farther south, additional studies within the Peninsular Ranges batholith demonstrated that it could be readily divided into an older, more westerly, magnetite-bearing suite and a younger, ilmenite bearing, high Sr/Y suite to the east Silver et al 1979;Silver and Chappell 1988;Kimbrough et al 2001;Tulloch and Kimbrough 2003).…”
Section: Introductionmentioning
confidence: 99%